An IPC Software Layer for Building a Distributed Virtualization System - Pessolani, Pablo Andrés (2017)
Hardware virtualization technologies were principally designed for server consolidation, allowing multiple Operating Systems instances to be colocated on a single physical computer. But, IaaS providers always need higher levels of performance, scalability and availability for their virtualization services. These requirements could be met by a distributed virtualization technology, which extends the boundaries of a virtualization abstraction beyond a host. As a distributed system, it depends on the communications between its components scattered in several nodes of a virtualization cluster. This work contributes M3- IPC, an IPC software layer designed to facilitate the development of an OS-based distributed virtualization.